THE DIALECTIC OF THE RELATIONSHIP BETWEEN PERTAKINA ADMINISTRATORS AND PERTAKINA MEMBERS IN ORGANIZATIONAL ACTIVITIES - Nurul Suhesti; Alo Liliweri; Dewi Widowati (Bajang Institute, 2023)
The phenomenon regarding Indonesian Migrant Workers (PMI) concerns the government in empowering their abilities after returning from working abroad. One non-governmental organization that houses the former PMI is the Association of Retired Workers and Families (PERTAKINA). The members who are former PMI are empowered in PERTAKINA organizational activities. There are organizational problems, namely the members' dissatisfaction with the management, which causes tension between the management and members. This research aims to find, understand and analyze the dialectics of the relationship between PERTAKINA and its members in organizational activities and to find the right relational communication model for PERTAKINA in organizational activities. This study uses Relational Dialectic Theory (RDT) to analyze these problems. The method used is a case study, with data collection techniques through interviews with PERTAKINA management and members and observation techniques in completing research data. The findings in the study indicate that members have dissatisfaction and distrust of the management, which causes tension in organizational activities. However, the members were reluctant to convey this openly to the organization's management, so it only became a conversation behind the management's back. Based on these findings, it becomes a new element in the relationship pole, namely tolerance as an element for Relational Dialectic Theory.